2016
DOI: 10.1002/pca.2665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring β‐Tubulin Inhibitors from Plant Origin using Computational Approach

Abstract: This is the first observation of inhibitory activity of isostrychnine against β-tubulin and warrants further experimental investigation. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Thus, computer aided drug designing and analysis can provide an insight into various unknown mechanisms (Karuppasamy et al, 2017;Purohit & Sethumadhavan, 2009). Docking and molecular dynamic studies are proved to be excellent tools in designing new drugs (Verma et al, 2017). In the case of COVID-19, many studies have provided a blueprint about the structure of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, computer aided drug designing and analysis can provide an insight into various unknown mechanisms (Karuppasamy et al, 2017;Purohit & Sethumadhavan, 2009). Docking and molecular dynamic studies are proved to be excellent tools in designing new drugs (Verma et al, 2017). In the case of COVID-19, many studies have provided a blueprint about the structure of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The ProTox calculation is based on 2D similarity to molecules exhibiting known LD50 values and on the recognition of chemical fragments that were overrepresented in compounds found to be toxic [46]. According to the Globally Harmonised System (GHS), toxicity is categorized into the six different classes based on LD50 range [47] published by the Occupational Safety and Health Administration (OSHA) [48] (Supporting Information Table S2).…”
Section: Admet Analysismentioning
confidence: 99%
“…The toxicity features (mutagenicity, tumorigenicity, irritant and reproductive effect) of the compounds were estimated based on the precompiled lists of fragments available using the Brazilian Archives of Biology and Technology. Vol.64: e21200402, 2021 www.scielo.br/babt algorithm that gives rise in the toxicity alerts in case that the compound structure is similar to that of the list of toxic fragments [48].…”
Section: Toxicity Feature Valuationmentioning
confidence: 99%
“…This drug interacts with the β-subunit of polymerised microtubules and prevents their depolymerisation, which, in turn, results in mitotic arrest and apoptosis. Verma et al (66) tried to identify a potent β-tubulin inhibitor using experimental and in silico approaches. For this purpose, compounds were extracted from Cassia fistula and their structure identified by GC-MS.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Searching the Naturally Occurring Plant-based Anticancer Compound-Activity-Target (NPACT) database, Verma et al (66) identified 1574 alkaloids with anticancer potential. Their pharmacokinetics and toxicity, binding efficiency, binding affinity of the docked complex, and metabolising capacity were evaluated by several computer programs.…”
Section: Natural Compoundsmentioning
confidence: 99%